The importance of using mobile ultrasound devices in improving the quality and safety of emergency care, anesthesia and intensive care - A. A. Krishtafor; D. A. Krishtafor; O. V. Kravets; O. V. Pylypenko (Сучасні медичні технології)
The aim of this review is to determine the role of ultrasound visualization in improving the safety and quality of anesthesia, intensive care and emergency medical care.